The Zong: A Massacre, the Law and the End of Slavery - Walvin, James (Yale University Press, 2011)
On November 29, 1781, Captain Collingwood of the British shipZongcommanded his crew to throw overboard one-third of his cargo: a shipment of Africans bound for slavery in America. The captain believed his ship was off course, and he feared there was not enough drinking water to last until landfall. This book is the first to examine in detail the deplorable killings on theZong, the lawsuit that ensued, how the murder of 132 slaves affected debates about slavery, and the way we remember the infamousZongtoday.Historian James Walvin explores all aspects of theZong's voyage and the subsequent trial-a case brought to court not for the murder of the slaves but as a suit against the insurers who denied the owners' claim that their "cargo" had been necessarily jettisoned. The scandalous case prompted wide debate and fueled Britain's awakening abolition movement. Without the episode of theZong, Walvin contends, the process of ending the slave trade would have taken an entirely different moral and political trajectory. He concludes with a fascinating discussion of how the case of theZong, though unique in the history of slave ships, has come to be understood as typical of life on all such ships.